Finding arboreal snakes in an evolutionary tree: phylogenetic placement and systematic revision of the Neotropical birdsnakes. (23rd December 2013) - Jadin, Robert C.; Burbrink, Frank T.; Rivas, Gilson A.; Vitt, Laurie J.; Barrio‐Amorós, César L.; Guralnick, Robert P.
Abstract The genus Pseustes Fitzinger, 1843 is composed of three recognized species, Pseustes poecilonotus, P. shropshirei and P. sulphureus, which may be the largest sized colubrid snake in the New World. The group has a complex systematic history that has yet to be untangled using modern molecular phylogenetic approaches. The systematic position, within‐group diversity and distribution are therefore uncertain. We obtained samples of four species from multiple specimens across their distribution and analysed one nuclear and two mitochondrial genes to determine the phylogenetic placement of the genus and infer relationships among Pseustes lineages. We find strong support for the paraphyly of Pseustes with respect to the monotypic genus Spilotes, both of which are nested within a clade of at least 23 other New World Colubrinae genera. Based on our results, we formally revise the taxonomy of P. poecilonotus and P. sulphureus, resurrecting the taxon P. polylepis for populations of P. poecilonotus from South America and allocating P. sulphureus to the genus Spilotes which renders both genera monophyletic. Additionally, we identify two lineages that are putatively new and currently unrecognized species. Finally, the placement of P. sulphureus, the type species of Pseustes, in the genus Spilotes, requires the allocation of the senior synonym Phrynonax be considered for the remaining Pseustes taxa.